DISTRIBUTION OF LOGISTICS ASSISTANCE FOR FLOOD VICTIMS IN PASANGKAYU REGENCY - Firdhayanti Iryadi; Ida Yunari Ristiani; Nadya Anggara Putri; Agus Supriatna (Institut Pemerintahan Dalam Negeri, 2024)
Disaster logistics assistance is an important element of disaster management efforts. Logistics distribution in disaster situations always faces complex challenges in distributing aid to victims affected by disasters. This research aims to provide an overview of how the distribution of logistical assistance to flood victims in Pasangkayu Regency and identify the inhibiting factors in the implementation of logistical assistance, and efforts that can be made by BPBD Pasangkayu Regency in overcoming these obstacles. This research uses a Qualitative Descriptive design with an Inductive approach. The data collection techniques used include observation, interviews, and documentation. The results showed that the logistics assistance distribution program had been carried out quite effectively, although there were still several factors that influenced the obstruction of the distribution, including limited human resources and lack of facilities and infrastructure in logistics distribution which resulted in not optimal distribution of logistics assistance in Pasangkayu Regency. The practical implication of this research is the importance of increasing the capacity of human resources, procuring adequate facilities and infrastructure, and better cross-sector coordination to ensure logistics distribution can run optimally and on time in emergency situations. Keywords: Logistic Aid Distribution, Flood Disaster, Logistics Management